Long Term Efficacy and Assessment of Tumor Response of Transarterial Chemoembolization in Neuroendocrine Liver Metastases: A 15-Year Monocentric Experience - Caroline Touloupas (MDPI AG, 2021)
Background: transarterial chemoembolization (TACE) is an established treatment for neuroendocrine tumor (NET) liver metastases. The aim was to evaluate the long-term treatment efficacy of TACE for NET liver metastases, and correlate imaging response with survival. Methods: this IRB-approved, single-center, retrospective study evaluated all TACE procedures performed for NET liver metastases from 2003–2017 for imaging tumor response (RECIST and mRECIST), time to liver progression (TTLP), time to untreatable progression with TACE (TTUP), and overall survival (OS). Patient, tumor, and treatment characteristics were analyzed as prognostic factors. Survival curves according to the Kaplan–Meier method were compared by Log-rank test. Tumor responses according to RECIST and mRECIST were correlated with OS. Results: 555 TACE procedures were performed in 202 NET patients (38% grade 1, 60% grade 2) with primary tumors originating from pancreas, small bowel, and lung (39, 26, and 22% respectively). Median follow-up was 8.2 years (90–139 months). Median TTLP and TTUP were 19.3 months (95%CI 16.3–22.3) and 26.2 months (95%CI 22.3–33.1), respectively. Median OS was 5.3 years (95%CI 4.2–6.7), and was higher among mRECIST responders (80.5 months; 95%CI 64.6–89.8) than in non-responders (39.6 months; 95%CI = 32.8–60.2; p < 0.001). In multivariable analysis, age, tumor grade and liver involvement predicted worse OS, whereas administration of somatostatin analogs correlated with improved OS. Conclusion: TACE for NET liver metastases provides objective response and sustained local disease control rates. RECIST and mRECIST responses correlate with OS.